Archaeological Field Survey in the Environs of Aldborough (Isurium Brigantum). (1st January 2018) - Dobinson, Colin; Ferraby, Rose; Lucas, Jason; Millett, Martin; Wallace, Lacey
Abstract: This paper presents the results of field surveys undertaken in 1987 and 1989–97 in the immediate vicinity of the Roman civitas capital of Isurium Brigantum (Aldborough, North Yorks). It presents the Roman finds from the survey, providing quantified analyses of pottery and ceramic building material as well as catalogues of the other artefacts collected. These studies provide new evidence for the history of the town and form the basis for a discussion of the development of the landscape in its environs, complementing other recent work at the site.